Meta-analysis on the safety and efficacy of Erdafitinib in treating FGFR1–4 mutated solid tumors - Huang, Jiyu; Wang, Zihan; Zhao, Fei; Aisa, Adilai; Tian, Shengkai; Chen, Siyuan; Peng, Lianyi; Yang, Xiaolu; He, Jianxin; Yang, Yue (Frontiers in Oncology, 2025)
ObjectiveThis article aims to analyze the safety and efficacy of Erdafitinib in the treatment of patients with advanced solid tumors harboring FGFR1–4 mutations.MethodsSearch for relevant articles in databases such as PubMed, Embase, The Cochrane Library, Web of Science, and CNKI, covering the period from their establishment to October 25, 2024. Summarize the adverse drug reaction (AE) data, overall survival (OS), median progression-free survival (PFS), objective response rate (ORR), and other relevant data for patients with advanced solid tumors treated with Erdafitinib for FGFR1–4 mutations. Conduct a meta-analysis on the corresponding summarized data using the software Stata 18.0.ResultsThrough our search, we identified a total of 10 articles involving 1019 patients. In urothelial carcinoma, the most prevalent adverse reactions are hyperphosphatemia (78.5%), diarrhea (56.5%), and stomatitis (51.1%). The most frequently reported adverse reactions in other solid tumors are hyperphosphatemia (66.5%), dry mouth (48.5%), and diarrhea (44.9%). Patients with urothelial carcinoma treated with Erdafitinib exhibit higher median progression-free survival (PFS) and objective response rate (ORR) compared to those treated with other solid tumor therapies.ConclusionCurrent evidence indicates that Erdafitinib exhibits certain therapeutic efficacy in the treatment of advanced solid tumors harboring FGFR1–4 mutations, with the most pronounced therapeutic effect observed in urothelial carcinoma. The efficacy of Erdafitinib in treating other solid tumors requires further confirmation through larger-scale studies involving a broader range of FGFR1–4 mutant tumors.